Selection and testing result of KT1 potato variety for fresh consumption and food processing in Northern provinces. - Thi Hue, Ngo; Thi Nhung, Nguyen; Van My, Trinh; Doan Dam, Ngo; Thu Huong, Nguyen Thi; Manh Quy, Nguyen; Huy Chien, Dao; Sharma, N.; Bonierbale, Merideth W. (2018)
Potato variety KT1 was selected from 27 introduced potato varieties from CIP in 2005. It had medium growth duration of 85 - 90 days. The average stem height of KT1 is about 60 - 70 cm, number of tubers/plant is from 6 - 10 tubers, yield from 20 - 25 tons/ha. KT1 potato variety is resistant to viral diseases, heat tolerant, slightly infected with late blight and main pests (aphids, mites, thrips) with light level. It’s tubers are of oval shape, shallow nodes, yellow tuber shell and pulp, high dry matter content of 21 - 23%; starch content from 14 - 17%, sugar-reduced content < 0.22% suitable for fresh consumption and food processing.